ANALISIS KECELAKAAN BERLALU LINTAS DI KOTA JAKARTA DENGAN MENGGUNAKAN METODE K-MEANS - Esty Purwaningsih (LPPM Nusa Mandiri, 2019)
In the city area of Jakarta, accidents in traffic enter problems that almost often occur at any time. Not a few victims suffered property damage, but victims also suffered minor injuries, serious injuries and even lost their lives. To analyze the number of accident incidents in traffic around the Jakarta city area which took casualties, researchers used a clustering method with the K-Means algorithm which was processed through rapidminer software. From the clustering of traffic accidents data obtained the level of accuracy in clusters 1 and 2 with the same accuracy that is equal to 20%, while cluster 3 gets an accuracy value of 10%